2022
DOI: 10.1007/s11355-022-00527-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and development of ornamental grasses on green roofs and living walls

Abstract: Ornamental grasses are often used in gardens to improve biodiversity and as additional aesthetical resources. However, their use in green roofs (GR) and living walls (LW) is not so widespread and it has not been studied extensively. The aim of this work is to assess the performance of seven grass species (Imperata cylindrica ‘Red Baron’, Acorus gramineus, Stipa tenuissima ‘Pony Fails’, Carex flagellifera ‘Bronzita’, Carex oshimensis ‘Evergold’, Uncinia rubra ‘Everflame’ and Miscanthus sinensis) for their use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…We observed differences in plant development depending on the climate and light conditions. Plants in LW do not grow so high, which could be due to less space for roots and the shoot (Suaŕez-Caćeres et al, 2022). The main difference between the experiment years was the hard winter between 2017 and 2018, where we observed that the plants needed more time to recover after the hard winter.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…We observed differences in plant development depending on the climate and light conditions. Plants in LW do not grow so high, which could be due to less space for roots and the shoot (Suaŕez-Caćeres et al, 2022). The main difference between the experiment years was the hard winter between 2017 and 2018, where we observed that the plants needed more time to recover after the hard winter.…”
Section: Discussionmentioning
confidence: 72%
“…Perennials that had the same genre compared to our study were: Achillea millefolia, Asplenium nidus, Bergenia ssp., Bergenia cordifolia, Carex brunnea, Carey morrowi, Geranium sanguineum, Iris sibirica, Polystichum rigens Tagawa, Tradescantia spathacea and Tradescantia zebrina. Also, ornamental grasses could be suitable for LW because they are visually attractive and need low maintenance (Suaŕez-Caćeres et al, 2022). At the beginning of our research, we hypothesised that we would find a higher variety of suitable plants for LWs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations